The Effect of Calcination Temperature on Crystal Structure of (Al,Cr)2O3 Solid Solution - Kallayalert, Yotin; Wongsawang, Chalo; Keawnuch, Benjamas; Busabok, Chumphol (Progress in Applied Science and Technology, 2019)
(Al,Cr)2O3 solid solutions were synthesized using aluminium oxide (Al2O3) and chromium oxide (Cr2O3) as the starting materials. These two oxide powders were mixed at 1:1 mole ratio using ball mill. Then the mixture was dried and calcined for 2 hours at various temperatures of 1,500 °C, 1,600 °C and 1,700 °C. The structures of the prepared powders were investigated by X-ray diffraction (XRD) technique. The XRD result showed that (Cr1-x, Alx)2O3 presented as a new phase in the calcined powders for all temperatures. The XRD pattern illustrated intensity of (Cr1-xAlx)2O3 peaks slightly increased and shifted to Al2O3 peaks when the calcination temperature increase, while intensity of Al2O3 peaks gradually decreased. From this result, it can be implied that Cr3+ in Cr2O3 rhombohedral structure was gradually substituted by Al3+ at high temperature. However, the completed reaction was clearly shown at 1,700oC. In addition lattice parameters (d-spacing 311 plane. a and c) were inversing with the calcined temperature.